Pilon Fractures: Update on treatment - Mombello , Franco; Vera, German; Rammelt , Stefan (Journal of the Foot & Ankle, 2024)
Tibial pilon fractures (plafond) are severe injuries resulting from predominately axial impaction. They are typically accompanied by severe damage to the vulnerable soft tissue envelope and the articular damage, making these fractures prone to complications. Treatment is individualized to the three-dimensional pathoanatomy, soft tissue damage, functional demands, compliance, and comorbidities of the affected patient. Most pilon fractures will benefit from stage management, which consists of primary closed reduction via ligamento taxis, external fixation, and secondary internal fixation after soft tissue consolidation. In the hands of an experienced team with all resources available, primary definite internal fixation seems to be associated with similar results and complication rates but faster rehabilitation. Primary fixation of the fibula is rarely helpful, and definite fixation is not necessary in every case. The choice of approaches is guided by the individual fracture pattern, which ensures minimal soft tissue and periosteal dissection. Minimally invasive techniques should be employed whenever feasible. The goals of pilon fracture treatment are anatomic reconstruction of the joint surface and stable axial realignment towards the tibial shaft, bridging any metaphyseal comminution with the least possible amount of soft tissue and periosteal stripping. The choice of implants, particularly the number of plates, should be balanced between absolute stability on one side and preservation of the blood supply to the bone and soft tissues and the chance of callus formation for faster bone healing on the other. Level of evidence V; Experience-Based Expert Opinion.